Enhanced Soluble Serum CD40L and Serum P-Selectin Levels in Primary Aldosteronism - Petramala, L.; Iacobellis, G.; Carnevale, R.; Marinelli, C.; Zinnamosca, L.; Concistrè, A.; Galassi, M.; Iannucci, G.; Lucia, P.; Pignatelli, P.; Ciardi, A.; Violi, F.; De Toma, G.; Letizia, C. (Hormone and Metabolic Research, 2016)
Primary aldosteronism (PA) is one of the most frequent forms of secondary hypertension, associated with atherosclerosis and higher risk of cardiovascular events. Platelets play a key role in the atherosclerotic process. The aim of the study was to evaluate the platelet activation by measuring serum levels of soluble CD40L (sCD40L) and P-selectin (sP-selectin) in consecutive PA patients [subgroup: aldosterone-secreting adrenal adenoma (APA) and bilateral adrenal hyperplasia (IHA)], matched with essential hypertensive (EH) patients. The subgroup of APA patients was revaluated 6-months after unilateral adrenalectomy. In all PA group, we measured higher serum levels of both sP-selectin (14.29±9.33 pg/ml) and sCD40L (9.53±4.2 ng/ml) compared to EH patients (9.39±5.3 pg/ml and 3.54±0.94 ng/ml, respectively; p<0.001). After removal of APA, PA patients showed significant reduction of blood pressure (BP) values, plasma aldosterone (PAC) levels and ARR-ratio, associated with a significant reduction of sP-selectin (16.74±8.9 pg/ml vs. 8.1±3.8 pg/ml; p<0.01) and sCD40L (8.6±1 ng/ml vs. 5.24±0.94 ng/ml; p<0.001). In PA patients, we found a significant correlation between sP-selectin and sCD40L with PAC (r=0.52, p<0.01; r=0.50, p<0.01, respectively); this correlation was stronger in APA patients (r=0.54; p<0.01 r=0.63; p<0.01, respectively). Our results showed that PA is related to platelet activation, expressed as higher plasma values of sCD40L and sP-selectin values. Surgical treatment and consequent normalization of aldosterone secretion was associated with significant reduction of sCD40L and sP-selectin values in APA patients.
Keywords: primary aldosteronism; platelet activation; CD40; p-selectin